Exploring the Use of Soft Systems Methodology and Business Model Canvas in Energy Service Companies - Sudarmaji, Eka; Yatim, Muhammad Rubiul; Masrio, Herlan (European Journal of Applied Sciences, 2023)
Changing the product sales-based business model to be service-based with user-oriented services (UOS) and Result-oriented services (ROS) or a combination is the best way to create a customer value proposition to stand out from competitive price competition. This study explores different business models for energy service companies (ESCOs). This research is based on a case study conducted between September 2021 to January 2023. This study uses action research based on the Soft System Methodology and uses an analogy through morphological analysis to explore alternative service-based business models (service domain). The question component of this study uses a business model canvas (BMC) framework. The in-depth interview determines what top management, customers, experts, and suppliers of energy-efficient products think about the service-based business model. This study found that companies can build alternative business models that represent how organizations create, deliver, and add value to products through service systems through analogous business models. This change in the business model benefits the company due to the increasing awareness of energy services companies for energy conservation and the limited number of energy service companies in Indonesia. The study suggests that ESCOs should consider a service-based business model and invest in resources and commitment. It can create a distinctive value proposition and differentiate itself from competitors. However, combining product, service, and sales system components (Product Service System (PSS) offered simultaneously to customers requires company resources and commitment.